Mechanochemical Synthesis of Zero Dimensional Organic‐Inorganic Metal Halide Hybrids. Issue 4 (16th September 2020) - Ben‐Akacha, Azza; Zhou, Chenkun; Chaaban, Maya; Beery, Drake; Lee, Sujin; Worku, Michael; Lin, Xinsong; Westphal, Riona; Ma, Biwu
Abstract: Mechanochemical synthesis has emerged as a facile method for the preparation of a wide range of organic, inorganic, and polymeric materials. Here, we report the use of mechanochemical synthesis for the preparation of ionically bonded organic metal halide hybrids with a zero‐dimensional (0D) structure at the molecular level. (Ph4 P)2 SbCl5 and (Ph4 P)2 MnCl4 were synthesized by grinding appropriate ratios of organic halide salt Ph4 PCl with inorganic metal halide salts SbCl3 and MnCl2, respectively. The structural and photophysical properties of mechanochemically synthesized (Ph4 P)2 SbCl5 and (Ph4 P)2 MnCl4 were characterized, which are almost identical to those of single crystals prepared by slow solution growth. By reacting Ph4 PCl with both SbCl3 and MnCl2, we have been able to produce a mixture of two 0D organic metal halide hybrids that exhibit a dual emission covering a wide range of the spectrum with Commission Internationale de l'Eclairage (CIE) coordinates of (0.4898, 0.4800). Our work has clearly established mechanochemical synthesis as an effective method to produce ionically bonded organic‐inorganic hybrids. Abstract : Mechanochemical synthesis is applied for the preparation of zero‐dimensional organic metal halide hybrids (Ph4 P)2 SbCl5 and (Ph4 P)2 MnCl4 . Their structural and photophysical properties were found to be almost identical to those of single crystals prepared via solution growth. A mixture of two 0D hybrids could be mechanochemically synthesized to exhibit dual emission.